2022
DOI: 10.1021/acsami.2c17797
|View full text |Cite
|
Sign up to set email alerts
|

Polarity Modulation Induced High Electrostrain Performance with Near-Zero Hysteresis in a (Sr0.7Bi0.2□0.1)TiO3-Based System

Abstract: High-precision piezo actuators necessitate dielectrics with high electrostrain performance with low hysteresis. Polarity-modulated (Sr 0.7 Bi 0.2□0.1 )-TiO 3 -based ceramics exhibit extraordinarily discrete multiphase coexistence regions: (i) the relaxor phase coexistence (RPC) region with local weakly polar tetragonal (T) and pseudocubic (Pc) short-range polar nanodomains and (ii) the ferroelectric phase coexistence (FPC) region with T long-range domains and Pc nanodomains. The RPC composition features a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The introduction of BSN induces noticeable changes in the shape and size of the domains. 63 In BNKT-0.0075BSN ceramics, a coexistence of ferroelectric domains and polar nano-microregions (PNRs) is evident. 64,65 With an increase in BSN content, the size and number of ferroelectric domains decrease and large ferroelectric domain structures are almost absent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of BSN induces noticeable changes in the shape and size of the domains. 63 In BNKT-0.0075BSN ceramics, a coexistence of ferroelectric domains and polar nano-microregions (PNRs) is evident. 64,65 With an increase in BSN content, the size and number of ferroelectric domains decrease and large ferroelectric domain structures are almost absent.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7A,B depicts the evolution of BNKT‐ x BSN structural domains characterized by piezoresponse force microscopy (PFM). The introduction of BSN induces noticeable changes in the shape and size of the domains 63 . In BNKT‐0.0075BSN ceramics, a coexistence of ferroelectric domains and polar nano‐microregions (PNRs) is evident 64,65 .…”
Section: Resultsmentioning
confidence: 99%
“…55 As depicted in Figure 5g− associated with an average size of polar nanodomains. 61, 62 The average autocorrelation functions C(r) are plotted with the average autocorrelation fitting, as shown in Figure 5j. The experimental data match well with the average autocorrelation fitting, and the fitted <ξ> value is presented in Figure 5k.…”
Section: Resultsmentioning
confidence: 99%
“…[48,49] Levin et al suggested that ½(ooe), ½(ooo) and ½(eoe) superlattices are manifested for orthorhombic Pb2 1 m symmetry with √ 2a p × √ 2a p × 2a p unit cell (alternative setting P2 1 ma). [50] Besides, atomic positions along [100] c are further analyzed using CalAtom Software [51,52] and then atomic displacement vectors are mapped in Figure 3e. According to schematic P directions of T and O phases along [100] c (Figure 3f [53,54] ), the visualized polar clusters of 1-2 nm with the same P T and P O directions are representative of T and O phases, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, atomic positions along [100] c are further analyzed using CalAtom Software [ 51,52 ] and then atomic displacement vectors are mapped in Figure 3e. According to schematic P directions of T and O phases along [100] c (Figure 3f [ 53,54 ] ), the visualized polar clusters of 1–2 nm with the same P T and P O directions are representative of T and O phases, respectively.…”
Section: Resultsmentioning
confidence: 99%